2008
DOI: 10.2478/s11536-008-0063-5
|View full text |Cite
|
Sign up to set email alerts
|

Career choice motivations of medical students and some characteristics of the decision process in Hungary

Abstract: AbstractThe changed circumstances of medical work, raises the question of how socio-economic changes over the last few decades has affected the professional socialisation of medical students. This paper explores the career choice motivations of medical students, as well as some characteristics of the process of making that choice and their effects on professional socialisation. The study was carried out with a self-administered questionnaire with 503 students in general medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…The results showed that the three top reasons for the study of Physiotherapy in South-Western Nigeria are 'Desire to help people optimize their physical health', 'Personal interest', 'Opportunity to work in a hospital setting'. These findings were partly in agreement with those of Mulnar et al (16) and Puljak et al (17) who reported that motivations and personal interest are the major factors that drive students toward medicine. Recommendation by parents, friends' or relatives who were physiotherapists did not play a major role.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that the three top reasons for the study of Physiotherapy in South-Western Nigeria are 'Desire to help people optimize their physical health', 'Personal interest', 'Opportunity to work in a hospital setting'. These findings were partly in agreement with those of Mulnar et al (16) and Puljak et al (17) who reported that motivations and personal interest are the major factors that drive students toward medicine. Recommendation by parents, friends' or relatives who were physiotherapists did not play a major role.…”
Section: Discussionsupporting
confidence: 92%
“…When they chose medical profession they might have been thinking of areas of occupation that are not strictly medical jobs in traditional sense, yet are done by people having a medical diploma. Previously such alternatives were relatively unknown while today they belong to the reality of the medical world [6,13].…”
Section: Discussionmentioning
confidence: 99%
“…Young people, who aimed to gain/ desired professional career, are more likely to choose medical career because they feel motivated and interested in helping people [13].…”
Section: Introductionmentioning
confidence: 99%
“…Dans un tiers des cas, les étudiants ont souhaité devenir médecins dès leur enfance. Ainsi, dans l'étude Molnar et al [32], 57 % des étudiants avaient pensé à choisir les études médicales dès leur enfance, alors que dans l'étude Millan et al [28], la majorité des étudiants avait souhaité s'engager dans la filière médicale dès la période de lycée.…”
Section: Discussionunclassified